2017
DOI: 10.1177/2309499017716254
|View full text |Cite
|
Sign up to set email alerts
|

Is minimally invasive surgery superior to open surgery for treatment of lumbar spinal stenosis? A systematic review

Abstract: This systematic review suggests that MIS reduces operating time, duration of hospital stay and CPK-MM levels. However, the evidence for these parameters is weak. Moreover, there is no conclusive evidence that MIS reduces reoperation or has better improvement in pain and outcome scores like VAS, SF-36 and JOA scores. The evidence is limited due to poor standardization of MIS definition, methodology and details of surgeon experience. MIS techniques should not be studied as a group, as each procedure is vastly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…By now, this minimally invasive approach is not considered the gold standard technology because of its rather steep "learning curve" and a significant risk of technical complications [23]. In addition, the available data is still insufficient to compare the open decompression and the minimally invasive technique used in the treatment of stenosis of the lumbar spine [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…By now, this minimally invasive approach is not considered the gold standard technology because of its rather steep "learning curve" and a significant risk of technical complications [23]. In addition, the available data is still insufficient to compare the open decompression and the minimally invasive technique used in the treatment of stenosis of the lumbar spine [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Open surgery is an effective method for the treatment; however, injuries to muscles and paravertebral ligaments due to large incisions during surgery may induce increased postoperative back pain and muscle atrophy [10,11]. One study showed that most open vertebral fusion procedures have longer hospital stays and may require more time for muscle recovery after surgery than minimally invasive fusion procedures [12].…”
Section: Limitations Of Conservative Treatment Versus Conventional Su...mentioning
confidence: 99%
“…A review of various conservative versus surgical treatment comparison studies published up to February 2015 found that surgery was associated with high complication and reoperation rates, whereas on the other hand, no side effects were reported for any of the conservative treatment options [17]. Even minimally invasive surgery for LSS did not significantly reduce operating time, length of hospital stay, or reoperation rates, nor did it offer better pain relief in outcome scores such as the visual analog scale (VAS), the 36-Item Short-Form Survey, and Japanese Orthopaedic Association scores [12]. However, a ten-year follow-up study of one hundred LSS patients who underwent either conservative therapy or surgical treatment found many with the former to have unsatisfactory outcomes that later became favorable after a subsequent switch to surgery, and there was no evidence of surgical treatment having worse outcomes in LSS patients with moderate to severe symptoms [18].…”
Section: Introductionmentioning
confidence: 98%
“…Treatment options for LSS are categorized as conservative and surgical; conservative therapies include pain medication, epidural injections, rehabilitation such as manual therapy with a hands-on physical therapist, aerobic training, and exercise intervention to treat patients with mild to moderate symptoms [7,11], and surgical intervention is considered if LSS symptoms do not improve with conservative therapies [12]. Surgeries aim to decompress the entrapped neural element or provide decompression through lumber fusion; for example, a split-spinous process for laminotomies and discectomies to correct LSS can minimize muscular trauma, maintain spinal stability, and easily re-enable movement, shorten the duration of hospital stays, reduce postoperative back pain, and provide satisfactory neurological and functional outcomes [13].…”
Section: Introductionmentioning
confidence: 99%